2010
DOI: 10.1007/s00296-010-1589-9
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between Poly(ADP-ribose) polymerase (PARP) polymorphisms and rheumatoid arthritis in a Korean population

Abstract: Several studies have investigated the roles of genetic polymorphisms in rheumatoid arthritis (RA). Some of these studies reported that polymorphisms of poly(ADPribose) polymerase 1 gene (PARP-1) are linked to rheumatoid arthritis. Poly(ADP-ribose) polymerase is an enzyme involved in DNA repair, genomic stability, apoptosis, gene transcription, proliferation, and autoimmunity. To determine whether genetic polymorphisms of PARP-1 are related to rheumatoid arthritis in a Korean population, six single nucleotide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
(41 reference statements)
1
3
0
Order By: Relevance
“…Bcl-2 mRNA and protein expression in hydrogen-mediated protection on PC-12 exposed to OGD/RP (Mo et al, 2019). PARP is an enzyme involved in DNA repair and apoptosis (Lee et al, 2012). In our study, we found that OGD treatment resulted in decreased expression of Bcl-2 and PARP in cortical neuronal cells.…”
Section: Discussionsupporting
confidence: 54%
“…Bcl-2 mRNA and protein expression in hydrogen-mediated protection on PC-12 exposed to OGD/RP (Mo et al, 2019). PARP is an enzyme involved in DNA repair and apoptosis (Lee et al, 2012). In our study, we found that OGD treatment resulted in decreased expression of Bcl-2 and PARP in cortical neuronal cells.…”
Section: Discussionsupporting
confidence: 54%
“…The role of PARP-1 in auto-reactive immune responses was shown for the first time in experimental models of rheumatoid arthritis (RA), a Th1 cell driven inflammatory autoimmune disease. In humans, an association between PARP-1 gene polymorphisms and RA was shown even if other studies reached contrasting conclusions [96,97]. A more recent study showed that a human RA-risk-associated non-coding polymorphism in the chemokine receptor CCR6 is a causal variant through which PARP-1 regulates CCR6 expression [98].…”
Section: Pathogenic Role In Non-cancer Diseasesmentioning
confidence: 99%
“…Lack of association was noted between PARP polymorphisms and rheumatoid arthritis in a Korean population (Lee et al, 2012). …”
Section: Figurementioning
confidence: 99%